1992
DOI: 10.1111/j.1474-919x.1992.tb04736.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection and coexistence of migrants and Afrotropical residents

Abstract: In this paper I discuss factors that influence the habitat choice of small migrant birds on their Afrotropical wintering grounds and the ecological isolation of migrants and residents. The main characteristic of migrants is the use of resources which are sporadic in space and time. The majority of migrants occur in seasonal savannas and open woodland, mostly using temporarily and locally abundant food sources generally unused by residents. Migrants are more eurytopic and exploit more open parts of the habitats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In the case of woodcreepers, the specialized adaptations for tree climbing [50] enhanced their performance in aggressive contests with some woodcreeper species on tree trunks [38]–[40], but compromised their performance in aggressive interactions with antbirds, which typically occur on small saplings and branches [44], [50]–[52]. In the case of migration, a fundamental trade-off appears to constrain the ability of species to excel at both migration and performance in aggressive interactions simultaneously (Text S3), resulting in smaller resident species dominating larger migrant species across many different environments [14], [53]–[55] …”
Section: Discussionmentioning
confidence: 99%
“…In the case of woodcreepers, the specialized adaptations for tree climbing [50] enhanced their performance in aggressive contests with some woodcreeper species on tree trunks [38]–[40], but compromised their performance in aggressive interactions with antbirds, which typically occur on small saplings and branches [44], [50]–[52]. In the case of migration, a fundamental trade-off appears to constrain the ability of species to excel at both migration and performance in aggressive interactions simultaneously (Text S3), resulting in smaller resident species dominating larger migrant species across many different environments [14], [53]–[55] …”
Section: Discussionmentioning
confidence: 99%
“…Several authors have noted differences in the primary habitat associations of migrants among the three major flyways (e.g. Leisler 1992;Mönkkönen et al 1992;Hockey 2000Hockey , 2005Boyle and Conway 2007), thus raising the question of what influences habitats may have in the different southern continents. In the western Palaearctic most migrants are denizens of early successional stages and more open habitats.…”
Section: Habitatsmentioning
confidence: 99%
“…Compelling evidence for the role of inter-specific competitive exclusion in the shaping of migrant and resident communities in the wintering grounds is lacking [2], [10], [12]. However, evidence for such competitive exclusion in an intra-specific context was provided by Perez-Tris and Telleria (2002) [23], who showed that resident blackcaps Sylvia atricapilla breeding in southern Spain maintained their breeding territories in primary forest habitats into the non-breeding season, while migrant blackcaps arriving at the start of the wintering season ‘leap-frogged’ into the secondary (lower quality) scrub habitats not occupied by residents.…”
Section: Introductionmentioning
confidence: 99%
“…adaptable) and have less restrictive habitat requirements during the non-breeding season, allowing them to use a wider range of winter habitat types than ecologically similar but more specialised resident species [2], [21], [24]. Such adaptability and breadth of foraging strategies has been shown in wintering golden orioles Oriolus oriolus , which were, by virtue of their wider range of foraging tactics, able to survive in lower quality microhabitats than were preferred by resident species [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation